Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 7 - Rational Functions - 7.3 Multiplying and Dividing Rational Expressions - 7.3 Exercises: 15

Answer

$= -\frac{(k+6)}{(k+9)} $

Work Step by Step

$\frac{(k+5)(7-k)}{(k-7)(k-3)} \times \frac{(k-3)(k+6)}{(k+9)(k+5)}$ $= \frac{(k+5)(7-k)(k-3)(k+6)}{(k-7)(k-3)(k+9)(k+5)} $ $= \frac{(7-k)(k-3)(k+6)}{(k-7)(k-3)(k+9)} $ $= \frac{(7-k)(k+6)}{(k-7)(k+9)} $ $= \frac{(-(k-7))(k+6)}{(k-7)(k+9)} $ $= \frac{-(k+6)}{(k+9)} $ $= -\frac{(k+6)}{(k+9)} $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.